2014
DOI: 10.1016/j.ijsu.2014.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic resection with or without mucosal ablation of high grade dysplasia and early oesophageal adenocarcinoma – Long term follow up from a regional UK centre

Abstract: ER ± ablation is an effective and potentially curative option for patients with HGD or IMC. The benefit of endoscopic resection for disease staging was clearly demonstrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Of these, 12 % (30/242) had received a rescue treatment (e. g. additional EMR, ESD, APC, or a combination of these) before CR-IM was achieved (▶ Table e2, available online-only). Treatment failed in 34 patients because of remaining IM (15), remaining dysplasia (11), need for surgery because of progression to adenocarcinoma (7) and there was one death due toe invasive adenocarcinoma. This was diagnosed on control biopsies after initial treatment with EMR and RFA (HALO 360) of long-segment Barrett's with previous histology of only HGD.…”
Section: Complete Remission Of Intestinal Metaplasiamentioning
confidence: 99%
“…Of these, 12 % (30/242) had received a rescue treatment (e. g. additional EMR, ESD, APC, or a combination of these) before CR-IM was achieved (▶ Table e2, available online-only). Treatment failed in 34 patients because of remaining IM (15), remaining dysplasia (11), need for surgery because of progression to adenocarcinoma (7) and there was one death due toe invasive adenocarcinoma. This was diagnosed on control biopsies after initial treatment with EMR and RFA (HALO 360) of long-segment Barrett's with previous histology of only HGD.…”
Section: Complete Remission Of Intestinal Metaplasiamentioning
confidence: 99%
“…The management of intramucosal OAC is relatively consensual since several studies found a very low risk of LNM, ranging from 0 to 1.8%, and an improved overall survival rate in patients treated by endoscopic means compared to surgery. [18][19][20][21][22] Pech and colleagues, in one of the largest cohorts of intramucosal OAC treated endoscopically found a 96.3% complete remission rate and a 0.2% tumour-related death rate following ER for intramucosal OAC. 22 However, a significantly higher risk of recurrence and failure of endoscopic treatment was reported in poorly differentiated intramucosal OAC in contradiction to our data where the LNM risk was still non-existent for intramucosal OAC regardless of the histoprognostic features.…”
Section: Discussionmentioning
confidence: 99%
“…The management of intramucosal OAC is relatively consensual since several studies found a very low risk of LNM, ranging from 0% to 1.8%, and an improved overall survival rate in patients treated by endoscopic means compared to surgery 18–22 . Pech and colleagues, in one of the largest cohorts of intramucosal OAC treated endoscopically found a 96.3% complete remission rate and a 0.2% tumour‐related death rate following ER for intramucosal OAC 22 .…”
Section: Discussionmentioning
confidence: 99%
“…Used alone or with other minimally invasive methods, such as endoscopic mucosal resection, PDT has been shown to eliminate Barrett's mucosa, destroy the HGD, and potentially reduce the rate of progression to adenocarcinoma. [70][71][72] Cancer of the Esophagus Cancer of the esophagus affects over 450,000 individuals per year worldwide with 400,000 deaths. 73 Over 50% of cases are surgically unresectable at diagnosis, and 80% are oncologically at a stage for which surgery cannot be undertaken with curative intent.…”
Section: Barrett's Esophagus and Esophageal Cancermentioning
confidence: 99%